تحضير ودراسة الليكاند 1، 1 - ثنائي ميثيل - 3 -"ثايازول - 2 آيل" ترايازين وبعض معقداته مع العناصر الانتقالية - حواس، محمود محمد; أبو راوي، ربيع مصطفى; زايد، جلال محمد (جامعة المرقب - كلية التربية بالخمس, 2020)
يتضمن هذا البحث تحضير الليكاند 1، 1- ثنائي ميثيل- 3- (ثايازول-2 ايل)- ترايازين من ازدواج املاح الدايازونيوم لــــ 2- امينو ثايازول مع الامين (ثنائي ميثيل امين) ومن تم مفعالة هذا الليكاند مع عدد من العناصر الانتقالية التي تشمل (Cu (II), Ni (II). تم تشخيص الليكاند المحضر بالطرق الطيفية باستخدام الاشعة تحت الحمراء IR ، وكذلك تحليل العناصر الدقيق C.H.N، وتعيين درجات الانصهار اما بالنسبة للمعقدات فبالإضافة الى القياسات السابقة تم قياس التوصيلية الكهربائية المولارية، والشكل البنائي المقترح لمعقدات النيكل (II) والنحاس(II).
The present work includes the synthesis of 1,1-dimethyl-3-( triazene -2-yl)-triazene by coupling diazonium salts for 2- amino thiazole with the amine (dimethylamine) which used as a ligand, to react with a number of transition metal ions including Ni (II) and Cu(II). The prepared compounds were identified by using IR, as well as C.H.N analysis. The melting point was also measured. Also the prepared complexes were determined by using IR, as well as C.H.N analysis. The molar conductivity was also measured for all complexes, and the proposed structure for Ni (II), and Cu (II) complexes.
Keywords: التفاعلات الكيميائية -- المركبات الحلقية -- المركبات العضوية